AKIBAT HUKUM ATAS PEMBATALAN SURAT KEPUTUSAN BUPATI TENTANG PEMBERHENTIAN KEPALA DESA SUMURBER KECAMATAN PANCENG KABUPATEN GRESIK - Eksan Eksan; Ainul Masruroh; Sholihan Sholihan (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2019)
The agency or the administrative office of the State does not necessarily succeed in carrying out its duties, sometimes the dispute arises due to a decision of the State administration that can cause dissatisfaction. The proposed termination of village chief conducted by the Village consultative Agency is not qualified as a reason to dismiss the head of Sumurber village, Panceng District, Gresik Regency. In addition to the State Administrative Decree/object dispute is contrary to government regulation about the village, also contrary to the regional regulation of Gresik Regency number 12 Year 2006 about the village government. On the other hand, the country's administrative decisions are contrary to good principles of government. Because the State Administrative Decree/object dispute is a state administrative decision contrary to good laws and principles of government. The author uses a method of scripting which provides the solution of legal case ATS that occur. This study analyzed the cancellation of decree of Regent of Gresik No. 141/678/HK/437.12/2013, dated 3 May 2013 concerning the dismissal of the village head of Sumurber, Panceng District, Gresik Regency. The decision of deliberation of the village consultative Agency related to the termination of the village head has been null and void, as a result of the Regent's decision on the termination of Sumurber village chief is irrevocable.